How Denmark, England, Estonia, France, Germany, and the USA pay for variable, specialized and low volume care: A cross-country comparison of in-patient payment systems - Quentin, Wilm; Stephani, Victor; Berenson, Robert A.; Bilde, Lone; Grasic, Katja; Sikkut, Riina; Touré, Mariama; Geissler, Alexander (Maad Rayan Publishing Company, 2022)
Background: Diagnosis-related group (DRG)-based hospital payment can potentially be inadequately low (or high) for highly variable, highly specialized, and/or low volume care. DRG-based payment can be combined with other payment mechanisms to avoid unintended consequences of inadequate payment. The aim of this study was to analyze these other payment mechanisms for acute inpatient care across six countries (Germany, Denmark, England, Estonia, France, the United States [Medicare]). Methods: Information was collected about elements excluded from DRG-based payment, the rationale for exclusions, and payment mechanisms complementing DRG-based payment. A conceptual framework was developed to systematically describe, visualise and compare payment mechanisms across countries. Results: Results show that the complexity of exclusion mechanisms and associated additional payment components differ across countries. England and Germany use many different additional mechanisms, while there are only few exceptions from DRG-based payment in the Medicare program in the United States. Certain areas of care are almost always excluded (eg, certain areas of cancer care or specialized pediatrics). Denmark and England use exclusion mechanisms to steer service provision for highly complex patients to specialized providers. Conclusion: Implications for researchers and policy-makers include: (1) certain areas of care might be better excluded from DRG-based payment; (2) exclusions may be used to incentivize the concentration of highly specialized care at specialized institutions (as in Denmark or England); (3) researchers may apply our analytical framework to better understand the specific design features of DRG-based payment systems.